PENGARUH KEDEKATAN EMOSIONAL DAN KOMITMEN TERHADAP LOYALITAS NASABAH PADA BSI KCP 1 ULEE KARENG BANDA ACEH - Khairunnisa, Khairunnisa; Inayatillah, Inayatillah (Program Studi Perbankan Syariah FEBI UIN Ar-Raniry, 2023)
The Efforts of Islamic Banks to survive in a very competitive market position is to maintain customer loyalty. The study aims to analize the effect of emotional closeness and commitment on customer loyalty with a quantitative approach. The population were all customers of BSI KCP 1 Ulee Kareng Banda Aceh, from which 99 respondens were drawn using purposive sampling technique. Data was analize using multiple linear regression that showed emotional closeness and commitment have no significant effect on customer loyalty either simultaneously or partially. It is hoped that BSI can improve good recriprocal relationships with customers.